Who gets more out of sport? The role of value and perceived ability in flow and identity-related experiences in adolescent sport - Drane, Cathy; Barber, B.L. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
© 2016, Copyright © Taylor & Francis Group, LLC.